Building a constitutional convention: Citizens and the UK's constitutional moment. Issue 1 (June 2015) - White, Stuart
<x xml:space="preserve">Abstract</x> Stuart White argues that the people, rather than parliament, must settle urgent questions about the basic composition of the UK's political system and the state's relationship to society. But settling on the design and remit of the required constitutional convention(s) may be a fraught process.